COMPARATIVE ANALYSIS OF FUTURE TENSES IN ENGLISH AND UZBEK LANGUAGES - Muxamadiyev A.Sh.; Jumayeva Roza Yunusovna (Лучшие интеллектуальные исследования, 2024)
Annotation: This article provides a comprehensive comparison of the future simple tense in English and Uzbek languages. The future simple tense is a grammatical structure used to express actions or events that are anticipated to occur in the future. The analysis focuses on the similarities and differences in the formation, usage, and semantic nuances of the future tenses in both languages. It examines the auxiliary verbs employed, the range of situations in which the tense is used, and the subtle variations in meaning that can arise.